Complexity: the Good, Bad and Ugly Aspects - Altshuler, Ernesto (Revista Cubana de Física, 2006)
Complexity is a fresh and dynamic branch of contemporary science, but also a fashionable label: it embraces, in principle, a huge amount of physical, mathematical, computational, biological and even sociological issues under a supposedly unified approach. “Emergence”, “Non linearity” and “Self organization” are some of the terms that come and go in this scenario; sometimes without a clear idea of what they mean in the context they were created. In general, physicists avoid such problems by trying to define Complexity as precisely as they can. However, I will show here that this is an extremely delicate task.